Implementation of Sanitation Practices in the Agricultural and Livestock Sectors to Support Environmental Health - Widya Ramadhini; Tumrat Tumrat (Jurnal EduHealth, 2026)
Sanitation plays an important role in maintaining environmental health and supporting sustainable agricultural and livestock production. This study aimed to evaluate the implementation of sanitation practices in Hiyung chili farming and cattle farming in Tambarangan Village, South Tapin Regency, South Kalimantan. A descriptive quantitative approach was employed through direct field observations, interviews with farmers and livestock breeders, and documentation of sanitation conditions. The assessment focused on five indicators: waste management, water quality management, facility cleanliness, biosecurity practices, and environmental conditions. The results showed that the overall sanitation score reached 80%, which was categorized as good. Facility cleanliness achieved the highest score, indicating that routine cleaning activities were consistently implemented in both agricultural and livestock sectors. Waste management and water quality management were also categorized as good, particularly through the utilization of cattle manure as organic fertilizer for Hiyung chili cultivation. However, biosecurity practices received a moderate score, suggesting the need for improved disease prevention measures and sanitation monitoring. Overall, the findings demonstrate that proper sanitation practices contribute positively to environmental health by reducing pollution risks, improving waste utilization, and supporting sustainable agricultural and livestock production systems. Continuous improvement in sanitation management and biosecurity implementation is recommended to enhance environmental sustainability in the study area.